Analisis Perbandingan Pembelajaran Individu dengan Pembelajaran Berkelompok Melalui Model Pembelajaran Kontekstual Mata Pelajaran Ekonomi terhadap Hasil Belajar di SMPN 1 Borbor - Hutapea, Devi Melati Winarti; Sinaga, Dearlina; Siahaan, Nova Yunita Sari (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The problem in this study is to find out how individual learning compares with group learning through the contextual learning model of economics subjects on learning outcomes at SMPN 1 Borbor on various materials of human needs and fulfillment tools with a sample of 60 students. The research method in this study is used with a quantitative method. The students' scores in individual learning through contextual learning have an average score of 78.7586 with a standard deviation of 6.836 and group learning through the contextual learning model has an average score of 88.6667 with, so it can be concluded that there is a significant difference between the variables X1 (individual learning through the contextual learning model) X2 (group learning through contextual learning). As a study conducted by Suhprihtin Siti, et al, the influence of economic learning with a contextual teaching and learning (CTL) approach on economic learning outcomes is reviewed from the initial ability of students